ASSESSING THE LEVEL OF SUSTAINABLE DEVELOPMENT OF RESTAURANT ESTABLISHMENTS WITH REGARD TO HACCP IMPLEMENTATION - Khrychov , S. O.; Chernushenko О. О.; Yudina , O. I. (Systems and Technologies, 2026)
The article substantiates an applied approach to assessing the level of sustainable development of restaurant establishments with regard to the maturity of HACCP-based procedures as a mandatory component of contemporary food safety management. The relevance of the research stems from the fact that, during wartime and economic turbulence, Ukrainian restaurant businesses are expected to ensure food safety, optimize resource use, reduce food waste, and maintain social resilience of personnel simultaneously. Based on the analysis of relevant scientific publications from 2021 to 2025, the paper demonstrates that prevailing sustainability assessment models in hospitality tend to prioritize environmental and economic indicators while insufficiently integrating food safety performance, food safety culture, and the quality of HACCP implementation. The methodology combines a systems approach, content analysis of recent scholarly sources, comparative analysis of regulatory requirements, integral assessment, and model-based testing on three typical restaurant profiles: a full-service urban restaurant, a quick-service deliveryoriented outlet, and a catering operator. An integral sustainable development index is proposed. It includes four indicator blocks: HACCP performance, environmental and resource efficiency, social responsibility, and economic-managerial resilience. The findings show that the strongest contributors to the overall sustainability score are systematic staff training, documented critical control points, food waste monitoring, energy and water control, and ingredient traceability. The model-based testing produced the following results: the catering operator achieved the highest integral index (0.81), followed by the full-service restaurant (0.76), while the quick-service delivery outlet showed a moderate score (0.69). The practical value of the study lies in the possibility of using the proposed instrument for internal audit, self-assessment, preparation for official inspections, and the design of resource-efficiency and circularity programs. The paper argues that the sustainable development of restaurant establishments should be interpreted not only through the triple bottom line logic but also through the operational reliability of food safety management systems, especially HACCP. Therefore, HACCP should be treated not as a narrow regulatory burden but as an enabling managerial platform that links consumer protection, process discipline, waste prevention, and long-term competitiveness in the restaurant sector.